Microwaves, a potential treatment for bacteria: A review - Zhang, Zhen; Wang, Jiahao; Hu, Yihe; Wang, Long (Frontiers in Microbiology, 2022)
Bacteria have brought great harm to the public, especially after the emergence of multidrug-resistant bacteria. This has rendered traditional antibiotic therapy ineffective. In recent years, hyperthermia has offered new treatments to remove bacteria. Microwaves (MW) are a component of the electromagnetic spectrum and can rapidly heat materials. Taking advantage of this characteristic of MW, related studies have shown that both thermal and nonthermal effects of MW can inactivate various bacteria. Even though the understanding of MW in the field of bacteria is not sufficient for widespread use at present, MW has performed well in dealing with microorganisms and controlling infection. This review will focus on the application of MW in bacteria and discuss the advantages, prospects and challenges of using MW in the bacterial field.